Fruit Crop Species with Agrivoltaic Systems: A Critical Review - Andrea Magarelli; Andrea Mazzeo; Giuseppe Ferrara (Agronomy, 2024)
As the world seeks alternatives to fossil fuels, agrivoltaics offer a promising solution by integrating solar panels with farming practices. This review examines three key agrivoltaic setups—static tilted, full-sun tracking, and agronomic tracking—dissecting their engineering features’ roles in optimizing both the electricity yield and the fruit productivity of some fruit crops. We emphasize the microclimatic modifications induced by agrivoltaic systems, mainly encompassing changes in solar radiation, air temperature, humidity, and wind. The data collected in this survey reveal a strong spatial heterogeneity distribution over different locations and a significant influence on fruit crops’ growth, yield, and quality, with variations among species. Such findings on the overall performance recommend a 30% shading threshold to prevent substantial declines in fruit characteristics, i.e., fruit yield and quality. Shading conditions over this threshold influence the leaf morphophysiological characteristics, impacting the photosynthesis capacity and fruit dry matter accumulation. This emphasizes the importance of further investigation into spectral radiation quality and carbon assimilation kinetics as daily responses for different fruit species to be cultivated in such new environments. Starting from this point, this review underscores the need to extend studies on various fruit crops, particularly those cultivated in semi-arid horticultural regions (i.e., for saving water), and suggests the use of comprehensive and standardized indicators for comparability across studies. Finally, the authors conclude that engineering improvements, along with new research programs on agrivoltaic systems, could lead to agricultural, environmental, and economic sustainability, as well as their practical implementation and attractiveness to farmers in the coming years.